2023
DOI: 10.1021/acs.energyfuels.3c02129
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Constraining Rate Coefficients in Fuel Oxidation Mechanisms Using Genetic Algorithm Optimization

Maria Demireva,
Leonid Sheps,
Nils Hansen

Abstract: Accurate fuel oxidation mechanisms can enable predictive capabilities that aid in advancing combustion technologies. High-level computational kinetics can yield reasonable rate coefficients with uncertainties, in some cases, below a factor of 2. Computed rate coefficients can be constrained further by optimizing against experimental data. Here, we explore the application of genetic algorithm (GA) optimization to constrain computed rate coefficients in complex fuel oxidation mechanisms in conjunction with tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In addition, H abstraction from THF by ˙OH to produce α-R˙ or β-R˙ also have relatively large sensitivity coefficients. In our recent work on constraining mechanism parameters through genetic algorithm optimization, we found that the modeled species concentrations in MPIMS experiments of CPT oxidation 34 and the mole fractions in JSR experiments on cyclohexane oxidation 46 were sensitive to two key reactions, (R1) and (R2).ROO˙ ↔ ˙QOOHROO˙ → HO 2 + co-productFor the present study, the HO 2 co-product in (R2) is DHF, as shown in Scheme 1. For THF, the sensitivity analysis finds (R1) to have a large sensitivity coefficient but not (R2).…”
Section: Resultsmentioning
confidence: 49%
“…In addition, H abstraction from THF by ˙OH to produce α-R˙ or β-R˙ also have relatively large sensitivity coefficients. In our recent work on constraining mechanism parameters through genetic algorithm optimization, we found that the modeled species concentrations in MPIMS experiments of CPT oxidation 34 and the mole fractions in JSR experiments on cyclohexane oxidation 46 were sensitive to two key reactions, (R1) and (R2).ROO˙ ↔ ˙QOOHROO˙ → HO 2 + co-productFor the present study, the HO 2 co-product in (R2) is DHF, as shown in Scheme 1. For THF, the sensitivity analysis finds (R1) to have a large sensitivity coefficient but not (R2).…”
Section: Resultsmentioning
confidence: 49%